Optimal cost benefit of the EToU electricity tariff for a manufacturing operation by using optimization algorithm - Sulaima, Mohamad Fani; Alias, Nur Umirah; Wan Abdul Razak, Intan Azmira; Sardi, Junainah; Bohari, Zul Hasrizal (Asian Research Publishing Network, 2021)
Since the electricity market are getting more attention due to the electricity demand, there are many options of tariff can be chosen thus making it harder for consumers to make decisions. The consumers must be searching for affordable tariff rate that able to give the benefit in reducing the total electricity cost. In regard to the issue, Tenaga Nasional Berhad (TNB) has introduced a more advanced tariff under Demand Side Management (DSM) programs namely Enhance Time of Use (EToU) tariff as an advanced version of the Time of Use (ToU) tariff for generation and demand side benefits. However, the number of participants has joined the program is under expectation due to less awareness and knowledge on the demand side management strategy. Thus, in this study, Simultaneous Demand Side Management (DSM) strategies are proposed for energy consumption cost reduction for a manufacturing energy load profile. Optimization algorithm namely Ant Colony Optimization (ACO) is implemented and cases with and without implementation of algorithm are compared in order to idealize the load profile of DSM strategy. The proposed method had shown reduction in electricity cost at all time zones of EToU tariff. The final result of this study is hopefully will contribute to help the industrial consumers in managing their tariff selection and to make demand side management program more acknowledgeable to the consumers.